Harlequin Ichthyosis: report of three cases (GAIMS Journal of Medical Sciences, 2022)
Harlequin Icthyosis is the most severe form of congenital Icthyosis. It characteristically presents as large thickened plate like scaly skin lesions over whole body at the time of birth. Few patients survive beyond neonatal period. Mortality is due to respiratory failure, hypo/hyperthermia, infections, electrolyte imbalance and dehydration.  Prevention of Harlequin Icthyosis can be done by prenatal genetic testing and counselling of parents. We are hereby reporting three cases of Harlequin Icthyosis in newborns.